OXIDATIVE STRESS AND EARLY POST-OPERATIVE COMPLICATIONS IN CARDIAC SURGERY - Zh. S. Filippovskaya; O. N. Gerasimenko; O. A. Grebenchikov; R. A. Zinovkin; R. N. Larkov; O. N. Ulitkina; Yu. V. Skripkin; V. V. Likhvantsev (Вестник анестезиологии и реаниматологии)
Cardiac surgery is often complicated by oxidative stress (the evidence of this is the increase of carbonyl proteins in blood plasma), however the relation between these changes and post-operative complications and unfavorable outcomes stills remains uninvestigated and lacks the relevant proof. The above facts served as a basis for this research. Goal of the article: to investigate the impact of oxidative stress assessed as per the level of carbonyl proteins in blood plasma on systemic inflammation response syndrome (SIRS), acute heart (AHF) and renal failure (ARF) in cardiac surgery. Methods. Prospective observational cohort study was conducted in order to investigate the relation of oxidative stress intensity, assessed as per the level of carbonyl peptides in blood plasma, and development of SIRS, AHF, ARF in the patients undergoing cardiac surgery. 67 adults patients admitted to Cardiac Intensive Care Department of M.F. Vladimirsky Moscow Regional Research Clinical Institute, Moscow, were examined. Results. The significant positive correlation has been found between intensity of oxidative stress assessed as per the level of carbonyl peptides in blood plasma, and composite frequency of post-operative complications (SIRS, AHF and ARF) in cardiac surgery (Spearman rank correlation (r) = 0.6; p < 0.0001). It was found out that the area under ROC-curve made 0.81 and 0.83 for the risk of developing acute renal lesions and heart failure respectively (p < 0.01 in both cases) thus the investigated model can be evaluated as "a model of very good quality". Conclusion. The important role pf oxidative stress in the development of SIRS, AHF and ARF has been confirmed. No advantages of off pump technique when performing coronary artery bypass grafting have been detected. Testing carbonyl peptides in blood plasma during first hours after surgery can be recommended in order to predict the risk of developing SIRS, AHF and ARF.